A web-based application for beekeepers to visualise patterns of growth in floral resources using MODIS data. (September 2016) - Arundel, Jonathan; Winter, Stephan; Gui, Guan; Keatley, Marie
Abstract: The honey bee industry is of immense importance to global agriculture. In many countries beekeepers are migratory and move their hives between flowering events. Predicting such flowering events is particularly difficult in Australia due to the irregular flowering of eucalypts. We have developed a web-based application for Victorian beekeepers to visualise patterns of growth in floral resources using MODIS and other data, and thus make remote predictions about whether flowering will occur at their apiary sites. We demonstrate the use of this application through comparing ironbark ( Eucalyptus tricarpa ) growth patterns with flowering and honey production records. While the scientific community as a whole has embraced the use of satellite imagery as a tool for phenological studies, our prototype represents the first attempt to make this same information available to a more general audience. Highlights: Commercial beekeeping in Australia is underpinned by the need to predict eucalypt flowering events from observations of budding and growth. Freely available satellite data, especially MODIS vegetation indices, can be used to remotely observe eucalypt growth. We have developed a web-based application, BeeBox, for beekeepers to make predictions of flowering across regions of interest. We use BeeBox to demonstrate agreement of growth, flowering and honey production data for Eucalyptus tricarpa .